The possibility of the event-based flight safety control taking into account the particular qualities of the pilot - B. I. Bachkalo; V. I. Zolotykh (Научный вестник МГТУ ГА)
The article analyzes the flight safety management process. The structure of the flight safety management system and the subjectobject interaction which is in the base of this system functioning are shown. The necessity of aircraft intelligent on-board control systems development and implementation is proved. The tasks that such systems will allow to solve during the flight are outlined. Application prospects of the real and documented flight safety contours in the system of active flight safety management are considered. The possibility of active flight safety control based on the parametric control principle is shown. The necessity of flight safety management based on the event-based control principle with the use of documented flight safety contour is proved. The example which visually demonstrates the capabilities and prospects of event-based flight safety management has been considered. The necessity of a particular pilot psychical characteristics taking into account while forming the contour of documented flight safety is proved. For this purpose, the flight personnel mental state systematic monitoring with the aim of professional suitability indicator determination expediency is justified. The possibility of using the pilot’s personal database for documented safety contour formation of each specific flight is considered in order to take into account the features of a particular pilot in managing flight safety. This should be a self-learning system that operates on the basis of the neural networks application and allows you to take into account all the characteristic and temperament features of each pilot in person. It is proved that the possibility of the pilot’s mental state taking into account, expressed by the value of the professional suitability indicator, can be successfully implemented exactly in the event of flight safety management, which will lead to the security increase of the aviation system from exposure of hazardous factors during the flight mission.